Handbook on the economics of the Internet - Bauer, Johannes; Latzer, Michael (Edward Elgar Publishing, 2016)
This handbook brings together twenty-six original chapters that discuss theoretical and applied frameworks for the study of the economics of the Internet, encompassing: its unique economics as a global information and communications infrastructure, the effects of the Internet on economic transactions, including social production, advertising, innovation, and intellectual property rights, the economics and management of Internet-based industries, such as search, news, entertainment, culture, and virtual worlds, and the effects of the Internet on the economy at large.